2020
DOI: 10.1080/21645515.2020.1840255
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination timeliness and completeness among preterm and low birthweight infants: a national cohort study

Abstract: Vaccinating premature and low birthweight (LBW) infants according to chronological age has been found safe and effective. Although these infants are susceptible to infections, vaccinations are often delayed. We estimated vaccination coverage (VC) in preterm and LBW infants compared to term infants in a cohort study (2016 Israel birth cohort, n = 181,543) using the National Immunization Registry. Vaccinations included Hepatitis B, Diphtheria-Tetanus-acellular Pertussis-IPV-Haemophilus influenzae B, Oral Polio B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
2
13
1
3
Order By: Relevance
“…For example, almost all the low birth weight (LBW) infants had both timely and complete vaccinations compared to normal weight infants. This is contrary to earlier reports where there were delayed vaccination of LBW infants ( 48 , 49 ). This is a concern because mortality of LBW infants has the highest contribution to under five mortality and death from VPDs due to delayed vaccination will be an unnecessary and avoidable added cause of mortality among this group of infants.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, almost all the low birth weight (LBW) infants had both timely and complete vaccinations compared to normal weight infants. This is contrary to earlier reports where there were delayed vaccination of LBW infants ( 48 , 49 ). This is a concern because mortality of LBW infants has the highest contribution to under five mortality and death from VPDs due to delayed vaccination will be an unnecessary and avoidable added cause of mortality among this group of infants.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies from other countries have found that infants born most preterm and with the lowest birth weight are less likely to receive vaccinations on time 5,7,13–17,23,28 . This international trend of vaccination delay has been ascribed to parents' and health workers' beliefs regarding preterm and low birth weight infants' frailty 3,23,28,29 . The reason the extremely preterm infants are more likely to receive vaccinations on time in our cohort could be explained by some of them still being hospitalised at the time of vaccination and by the recommendation in Denmark of in‐hospital vaccination for the first childhood vaccination.…”
Section: Discussionmentioning
confidence: 73%
“…PTB and LBW were common reasons for delayed vaccination, as parents or doctors perceive preterm and low birth weight infants as medically fragile even after their health has improved and their weight increased. 19 , 26 …”
Section: Discussionmentioning
confidence: 99%